Overall Survival With Maintenance Olaparib at a 7-Year Follow-up in Patients With Newly Diagnosed Advanced Ovarian Cancer and a BRCA Mutation: The SOLO1/GOG 3004 Trial. Issue 1 (January 2023) - DiSilvestro, Paul; Banerjee, Susana; Colombo, Nicoletta; Scambia, Giovanni; Kim, Byoung-Gie; Oaknin, Ana; Friedlander, Michael; Lisyanskaya, Alla; Floquet, Anne; Leary, Alexandra; Sonke, Gabe S.; Gourley, Charlie; et al.
Abstract : (Abstracted from J Clin Oncol 2022; doi: 10.1200/JCO.22.01549) Because of nonspecific symptoms at disease presentation and inadequate screening methods, ovarian cancer is often advanced at the time of diagnosis results in a 10-year survival of 17% in patients with advanced epithelial ovarian cancer. The poly(ADP-ribose) polymerase (PARP) inhibitor olaparib is the new standard of care in patients with newly diagnosed advanced ovarian cancer and a BRCA1 and/or BRCA2 (BRCA) mutation.